Extracorporeal Membrane Oxygenation for Pediatric Toxin Exposures: Review of the Extracorporeal Life Support Organization Registry. Issue 6 (10th August 2022) - Koshel, Christine K.; Alexander, Peta M.A.; Rycus, Peter; Alibrahim, Omar
Abstract : Evidence for the use of extracorporeal membrane oxygenation (ECMO) in children with refractory respiratory failure or shock following ingestion or toxin exposure, has been confined to single-center experiences, individual case reports, and extrapolated from adult cohorts; no pediatric multicenter cohorts exist. The objective of this retrospective review of the Extracorporeal Life Support Organization registry is to describe pediatric ECMO use following ingestion or toxin exposure, and define factors associated with mortality. Twenty-eight children between the ages of 30 days and 18 years met inclusion criteria between January 1, 2008 and December 31, 2017. The primary outcome measure was mortality before hospital discharge, which occurred in 32% of patients. Factors associated with in-hospital mortality included pre-ECMO use of inhaled nitric oxide (44.4% vs. 5.3%, p = 0.026), lower pre-ECMO arterial blood gas pH (6.97 [6.80–7.17] vs. 7.20 [7.15–7.32], p = 0.034), and higher pre-ECMO PaCO2 (79 [57–85] vs. 49 [38–63], p = 0.014). Receipt of inotropic support during ECMO was more common in nonsurvivors (66.7% vs. 21.1%, p = 0.035). Extracorporeal membrane oxygenation should be considered in the most severe pediatric toxin exposures as a bridge to recovery, providing time for both toxin elimination and end-organ recovery.